Acute adrenal haemorrhage in two cats with aldosterone-secreting adenocarcinomas. Issue 1 (April 2019) - Kirkwood, Nicolle; Boland, Lara; Brunel, Laurencie; Wardman, Alison; Barrs, Vanessa R
Case summary: Two 13-year-old domestic shorthair cats were diagnosed with unilateral right adrenocortical carcinomas (ACCs) and primary hyperaldosteronism (PHA). Both had polyuria, polydipsia and weight loss, and developed severe anaemia from an episode of acute adrenal haemorrhage. In one case, this occurred during hospitalisation and treatment of severe muscle weakness with cervical ventroflexion, while the other cat had acute collapse at home. A diagnosis of PHA was confirmed in both cases based on measurement of plasma aldosterone and renin activity. In one case, basal progesterone was also measured and was elevated. On ultrasonography and CT in one case, haemorrhage into the right retroperitoneal space was identified. Unilateral adrenalectomy was performed in both cases and there was no evidence of venous tumoral invasion in either. On histopathology of the excised adrenal glands both were ACCs with tumour necrosis, and one had extensive intratumoral haemorrhage. Both cats were diagnosed with International Renal Interest Society stage 2 or 3 chronic kidney disease postoperatively; one survived for 18 months and the other was well 8 months postoperatively. Relevance and novel information: Acute adrenal haemorrhage secondary to adrenal neoplasia has been reported in only one other cat, in which tumour type and function were not specified. Acute adrenal haemorrhage can occur as a consequence of tumour necrosis and rupture and can cause severe hypovolaemia and anaemia in cats with primary hyperaldosteronism.